Susceptibility of cassava varieties to disease caused by Sri Lankan cassava mosaic virus and impacts on yield by use of asymptomatic and virus-free planting material - Malik, Al Imran; Sophearith, Sok; Delaquis, Erik; Cuéllar, Wilmer Jose; Jiménez Polo, Jenyfer; Newby, Jonathan Craig (MDPI, 2022)
Cassava (Manihot esculenta Crantz) is a rainfed, smallholder-produced crop in mainland Southeast Asia, and is currently facing a serious challenge posed by the introduction of cassava mosaic disease (CMD). This study assessed the susceptibility of popular Asian varieties to CMD, yield penalties associated with the disease, and the efficacy of selecting clean or asymptomatic plants as seed for the following season. Field experiments evaluated agronomic management practices (ie, fertilizer application, use of symptomatic and asymptomatic seed stakes) in Cambodia with six to nine popular varieties over three seasons under natural disease pressure. Popular cassava varieties KU50 and Huaybong60 showed superior CMD tolerance, with consistently fewer symptomatic plants, lower disease progress measures, and higher yields. Plants demonstrating symptoms at early stages of development, ie, 60 days after planting, yielded significantly less than those developing symptoms later (ie, 270 DAP) or not at all. Plants grown from clean stems yielded on average 20% to 2.7-fold higher than those grown from symptomatic planting material. A yield decline of~ 50% was recorded with symptomatic planting materials of susceptible varieties (eg, SC8,~ 25 t ha− 1) over successive years. The findings emphasize that farmers could use positive selection by choosing asymptomatic plants to significantly reduce yield losses.